Effectiveness of warm compresses on the incidence of perineal rupture in phase II labor - Selvia; Dona, Sismeri; M. Fajriannor; Handayani, Lisda (Health Sciences International Journal, 2025)
Background: Perineal rupture is a common complication during the second stage of labor, particularly among primiparous women, leading to maternal morbidity. Warm compresses have been suggested as an intervention to reduce perineal rupture by promoting muscle relaxation and elasticity. However, their effectiveness remains inconclusive. Objective:   To analyze the effect of warm compress application on the incidence of perineal rupture during the second stage of labor in primiparous women. Method:  This quasi-experimental study employed a pre-test and post-test design involving 10 primiparous women at 18 to 29 years old divided into intervention (n=5) and control (n=5) groups. Warm compresses were applied for 20 minutes during the second stage of labor in the intervention group. Data were collected using partograph sheets and analyzed using descriptive and inferential statistics, with a significance level of p<0.05. Result:  Among the intervention group, 40% experienced no laceration, 20% had first-degree laceration, and 40% had second-degree laceration. In the control group, 40% had no laceration, and 60% suffered second-degree laceration. Statistical analysis showed no significant difference in the incidence of perineal rupture between the groups (p=0.452). Conclusion:  Warm compresses did not significantly reduce the incidence of perineal rupture during the second stage of labor. Further research with a larger sample size and broader variables is recommended to validate these findings.